2009
DOI: 10.1371/journal.pone.0008054
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficient FLPo Deleter Mice in C57BL/6J Background

Abstract: Conditional gene manipulation in mice becomes a routine for genetic studies of mammalian gene functions. Additional site-specific recombinases such as FLP or φ31 provide one more level of gene manipulation flexibility. The recombination activity of the currently available FLP deleter mice remains low. We generated a new FLP deleter mouse line with the mouse codon-optimized FLPo gene in C57BJ/6 background, which showed superior recombination efficacy in comparison to FLPe deleter mice. 100% complete removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 18 publications
3
51
0
Order By: Relevance
“…C57Bl/6J fertilized oocytes (Wu et al, 2009). In concordance with our results, one of those PGK-Flpo lines showed complete recombination of FRT-flanked reporters and it was superior to the Flpe deleter line.…”
Section: Generation Of Caggs-fipo Es Cells and Micesupporting
confidence: 90%
“…C57Bl/6J fertilized oocytes (Wu et al, 2009). In concordance with our results, one of those PGK-Flpo lines showed complete recombination of FRT-flanked reporters and it was superior to the Flpe deleter line.…”
Section: Generation Of Caggs-fipo Es Cells and Micesupporting
confidence: 90%
“…28 This was independently verified in several contributions demonstrating increased efficiency of Flpo relative to Flpe in deleting sequences flanked by equi-directed FRT. 8,29 Engineering Cre and Flp proteins for nuclear transfer For proteins N45 kDa in size, transport into the nucleus requires specific targeting sequences, called nuclear localization signals (NLS), which mediate interaction with the nuclear transport machinery. 30 It has been suggested that the 38-kDa Cre protein enters the nucleus by passive diffusion, as the addition of a highly efficient NLS from the SV40 large-T antigen did not alter its nuclear localization.…”
Section: Origin Of the Relevant Integrasesmentioning
confidence: 99%
“…A Flp recombinase mutant that is stable at 37C has been developed to improve recombination efficiency at 37C in order to use cultured cells, ES cells, and mice with maximal recombination efficiency (4). VCre originated from a plasmid derived from Vibrio sp., and SCre originated from a plasmid derived from Shewanella sp., ANA-3.…”
Section: Resultsmentioning
confidence: 99%
“…However, the recombination efficiency of the Flp/FRT system is less than that of the Cre/loxP system. To improve recombination efficiency, some researchers have attempted to optimize Flp by introducing mutations that convert it into a thermostable FLP mutant (3) and by altering its codon usage (4). Additionally, there are currently other genomic engineering tools available such as Dre recombinase (5), which recognizes the 32-bp long rox site, and PhiC31 (6) and R4 (7) integrases.…”
mentioning
confidence: 99%